Queen of storms - Feist, Raymond E. (Feist, Raymond E. Firemane, 2021)
"Hatushaly and his young wife Hava, are not the ordinary, loving couple they appear to be. They are assassins from the mysterious island of Coaltachin, home to the powerful and lethal hidden warriors known as nocusara. Posing as innkeepers in the trading town of Beran's Hill, they await insturctions from their masters in the Kingdom of Night. But Hatu conceals an even more dangerous secret. He is the last remaining member of the legendary Firemanes, the ruling family of Ithrace. Known as the Kingdom of Flames, Ithrace was one of the five greatest realms of Tembria, ruled by Hatu's father until he and his people were betrayed. Hatu--then a baby--was hidden among the nocusara, who raised him to become a deadly spy. Even as Hatu hides his true identity, unexpected calamity forces him to make choices he could not have dreamed awaited him. A series of horrific events shatters the peace of Beran's Hill, bringing death and devastation and unleasing monstrous forces. Once more, the Greater Realms of Tembria are threatened--and nothing will ever be the same again"--Page 4 of cover